Medicamentos psicotrópicos : concepções do uso a partir das perspectivas do usuário, do familiar que cuida e do profissional que o utiliza como recurso de cuidado, no contexto da Atenção Básica - Cavalcante, Deisiluce Miron (2017)
The medicalization has long been constituted as a social phenomenon, based on the principles of biomedical rationality. Given this context, the present research sought to investigate the conception of users, family members and health professionals regarding the use of the psychotropic medication in the therapeutic process, in the setting of Primary Care. The study had as a scenario the family health unit (USF), in the city of Aracaju, classified as a reference in mental health. The method used runs through the presuppositions of qualitative research, having as an instrument of investigation and data collection the narrative. It counted with the collaboration of 18 interlocutors, among them 10 professionals, 6 users and 2 family members. The data collection took place from the insertion of the researcher in the field, through the productions of field diaries and narrative of the participants. Data analysis was performed by reading / re-reading these productions, interpreting and highlighting data relevant to the research question. With this, it was possible to know a little of the observed reality, having as highlight the presence of the medical practices. It was perceived that the USF currently constitutes a device that contributes to the strengthening of the medicalization process. Regarding conceptions about the psychotropic drug: users perceive this use ambivalently, considering that it is good and bad to use it as a strategy of care, good in the sense of redeeming symptoms, and bad for the appearance of undesirable effects; family members see the medicine as very good because it helps them deal with problems presented by their relatives; and finally, the professionals, who despite highlighting the undesirable effects caused by the use, see the medication as necessary in the containment and control of the symptoms that the users present. Thus, the study brought a discussion about these aspects, concluding on the importance of the planning of actions that can contribute to the establishment of strategies of care, besides the medical practices, that bring benefits to the users, their relatives and to the network of health care; Of the articulation of the care network and, in particular, sought to contribute to the expansion of empirical studies that involve the theme.